2016
DOI: 10.1073/pnas.1610176113
|View full text |Cite
|
Sign up to set email alerts
|

Merkel disc is a serotonergic synapse in the epidermis for transmitting tactile signals in mammals

Abstract: The evolution of sensory systems has let mammals develop complicated tactile end organs to enable sophisticated sensory tasks, including social interaction, environmental exploration, and tactile discrimination. The Merkel disc, a main type of tactile end organ consisting of Merkel cells (MCs) and Aβ-afferent endings, are highly abundant in fingertips, touch domes, and whisker hair follicles of mammals. The Merkel disc has high tactile acuity for an object's physical features, such as texture, shape, and edges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 30 publications
7
82
3
1
Order By: Relevance
“…Future studies on the morphogenesis of Merkel cells are important not only for our understanding of the biology of the skin as a sensory organ but also for uncovering processes that lead to human pathologies. Hyper‐ or hypo‐sensitivity to touch have long been reported in patients with diabetes, inflammation or autism . Recent studies have shown that Merkel cells can inhibit alloknesis, a disease state where mechanical light touch stimuli provoke itching .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies on the morphogenesis of Merkel cells are important not only for our understanding of the biology of the skin as a sensory organ but also for uncovering processes that lead to human pathologies. Hyper‐ or hypo‐sensitivity to touch have long been reported in patients with diabetes, inflammation or autism . Recent studies have shown that Merkel cells can inhibit alloknesis, a disease state where mechanical light touch stimuli provoke itching .…”
Section: Discussionmentioning
confidence: 99%
“…Hyper-or hypo-sensitivity to touch have long been reported in patients with diabetes, inflammation or autism. [33][34][35][36] Recent studies have shown that Merkel cells can inhibit alloknesis, a disease state where mechanical light touch stimuli provoke itching. [37] Finally, these discoveries might help us uncover which mechanisms control Merkel cell carcinoma, a deadly skin disease with no effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the fingertip and hairy skin, decades of work have characterized responses of slowly adapting (SA) type 1 afferents, which correspond to large-diameter nerve fibers that associate with Merkel cells in the skin (Iggo and Muir, 1969; Woodbury and Koerber, 2007). Recent work has shown that mechanical activation of Piezo channels drives spiking in both Merkel cells and their afferents (Ikeda et al, 2014; Maksimovic et al, 2014; Ranade et al, 2014; Woo et al, 2014), and that Merkel cells synaptically excite their afferents (Chang et al, 2016; Maksimovic et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Although metabotropic 5-HT receptors do not directly permit current flowing through, previous studies have shown that activation of 5-HT 2A/2C and 5-HT 7 receptors could elicit inward currents through the potentiation of I h currents (Tang and Trussell, 2015). We have recently shown in mouse whisker afferent neurons that serotonin evoke fast and slow currents by activating 5-HT 3 and 5-HT 2A/2B receptors, respectively (Chang et al., 2016). …”
Section: Discussionmentioning
confidence: 99%